Characterization of Soils of Narasinghpur Block in Cuttack District of Odisha - Lilan Kumar Behera; Ramawatar Meena; Pragnya Paramita Patel; S.K. Verma; R.N. Meena (Journal of the Indian Society of Soil Science, 2023)
This experiment was carried out to characterize the soils of the study area through the profile study in Cuttack district of Odisha state. In this experiment 15 villages were selected for the profile study. Four samples were collected from each profile from four depths (0-15, 15-30, 30-60 and 60-90 cm). Depth-wise soil samples were processed and analysed for soil texture, bulk density, particle density, porosity, soil pH, electrical conductivity (EC), organic carbon (OC), available nitrogen (N), phosphorus (P), potassium (K), sulphur (S), iron (Fe), zinc (Zn) copper (Cu) and manganese (Mn). Results of soil analysis revealed that soil texture of the studied area was sandy loam and sandy clay loam. Bulk density increased with the increasing depth of the profile and found in the range between 1.23 to 1.45 Mg m-3. The pH values of the soils of the studied area were neutral to slightly alkaline and EC was <1 dS m-1. The average OC of the surface soil was slightly medium, which reduced with the increasing depth of the profile. Nitrogen content of the studied area was in the medium range and decreased in the soil profile up to 90 cm depth. Phosphorus content was in the medium range and K content was in high range and both decreased in the soil profile with the increasing depth. Soils of the study area were deficient in S content. Micronutrients (Fe, Zn, Cu and Mn) were slightly higher than the critical limits and reduced gradually along with the depth of soil profile.